Design of an Optimal Testbed for Acoustic Tags: Test Case for Marine Megafauna - Alexandri, Talmon; Diamant, Roee (Frontiers in Marine Science, 2022)
Underwater acoustic technologies are a key component for exploring the behavior of marine megafauna such as sea turtles, sharks, lobsters, and seals. The animals are marked with acoustic devices (tags) that periodically emit signals encoding the device's ID, depth, temperature, or the dominant acceleration axis - data that is collected by a network of deployed receivers. In this work, we aim to optimize the locations of receivers for best tracking of acoustically tagged marine megafauna. The outcomes of such tracking allows the evaluation of the animals' motion patterns, their hours of activity, and their social interactions. In particular, we focus on how to determine the receivers' deployment positions to maximize the coverage area in which the tagged animals can be tracked. For example, an overly-condensed deployment may not allow accurate tracking, whereas a sparse one, may lead to a small coverage area due to too few detections. We formalize the question of where to best deploy the receivers as a non-convex constraint optimization problem that takes into account the local environment and the specifications of the tags, and offer a sub-optimal, low-complexity solution that can be applied to large testbeds. Numerical investigation for three stimulated sea environments shows that our proposed method is able to increase the localization coverage area by 30%, and results from a test case experiment demonstrate similar performance in a real sea environment. We share the implementation of our work to help researchers set up their own acoustic observatory.